Word Stress Contribution in Second Language Acquisition - Patricia Angelina Lasut (Universitas Sanata Dharma, 2015)
Possessing native-like pronunciation is one of the main goals that non-native speakers of English would like to accomplish. Besides the ability to pronounce English sounds correctly, using the proper English word stress also plays an important role in achieving that goal.This paper first specifies the nature of word stress in English and its contribution on successful English language learning. Secondly, it addresses the problems that are commonly encountered by the Indonesian learners in using correct word stress in their speech. Finally, it also proposes some ways that English learners can use to learn English word stress better. Hopefully these proposed ways will be able to help the learners to speak in English more fluently with not only accurate pronunciation but also with correct word stress.